Epidemiological Study of Otodectes cynotis Infestation in Pet Cats in Urban Areas (Case Study in Mataram City) - Katty Hendriana Priscilia Riwu; Maratun Islamiah; Akhmad Sukri; Erprinanda Galuh Berliana; Soca Karina; Alifianita Anake Yansri; Freshindy Marissa Wibisono; Sesa Puput Febriyanti; Laily 'Ulya Nurul 'Ilmi; Aprinda Ratna Lovela (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2026)
Otodectes cynotis is a parasitic mite frequently identified in the external ear canal of cats, where it causes otitis externa and severe pruritus. Environmental conditions, hygiene standards, and animal management practices influence the prevalence of this mite. The present study aimed to assess the detection rate and prevalence of O. cynotis infestation in cats presented to veterinary clinics in Mataram City, West Nusa Tenggara. A total of 63 cats from three clinics (A, B, and C) were examined between November and December 2024. Earwax samples were processed using the native method with a 10% KOH solution at the Parasitology and Microbiology Laboratory, Faculty of Veterinary Medicine, Mandalika University of Education. Microscopic examinations at 10× and 40× magnifications were conducted to identify O. cynotis based on morphological characteristics. Among the 63 cats examined, 22 (34.92%) were found to be infested. The prevalence rates were 40.74% at Clinic A, 29.17% at Clinic B, and 33.33% at Clinic C. These results demonstrate a moderate to high prevalence of O. cynotis among cats in Mataram City. Routine ear examinations, enhanced hygiene practices, and regular antiparasitic treatments are recommended to reduce infestation rates and improve feline ear health. Keywords: Otodectes cynotis, cats, prevalence, ear mite, Mataram City